Implementasi Sistem Pelaporan Digital untuk Penguatan Data Lingkungan di Kelurahan Padurenan - Prayitno, M Hadi; Tomatala, Orodeo; Saputra, Bayu Rahman; Sodik, M Jafar; Nurdiansyah, Muhammad Sidik; Pahlevi, Muhammad Reza; Hakim, Riyan Fauzi (Journal Of Computer Science Contributions (JUCOSCO), 2025)
The administrative data management at the Neighborhood Association (RT) and Community Unit (RW) levels in Padurenan Village is still predominantly manual, leading to inefficiencies, risks of data loss, and low community participation in reporting. Through a Community Service Program (KKN), an Excel-based reporting system was implemented to enhance the performance and involvement of local community administrators. The program involved several stages: initial coordination with village officials, field surveys to identify needs, system design, socialization, and hands-on training for RT/RW administrators. Program evaluation was conducted through direct observation and feedback from users during the implementation phase. The results indicate a significant increase in the digital literacy of RT/RW administrators, enabling more structured, efficient, and accurate data recording. This digital transformation has also fostered greater community participation in administrative activities. The program successfully established a foundational digital administration system, replacing manual methods with a more organized and accessible approach. Recommendations for future development include periodic system updates and ongoing training to ensure the sustainability of this digital initiative.